Perceptions of cervical cancer and motivation for screening among women in Rural Lilongwe, Malawi: A qualitative study - Bula, Agatha K.; Lee, Fan; Chapola, John; Mapanje, Clement; Tsidya, Mercy; Thom, Annie; Tang, Jennifer H.; Chinula, Lameck (PloS one, 2022)
Cervical cancer is the leading cause of cancer death among women in Malawi. Low awareness of cervical cancer and negative perceptions of screening can prevent women from participating in preventative strategies. We sought to explore perceptions and motivations for screening among women who participated in a cervical cancer screen-and-treat pilot study in rural Malawi. We conducted a qualitative sub-study of a community-based cervical cancer screen-and-treat pilot study in rural Lilongwe between July-August 2017. From October 2017-February 2018, 17 women who underwent screening using visual inspection with acetic acid (VIA) and same-day thermal ablation treatment were recruited at their 12-week follow-up visit post treatment to participate in this qualitative sub-study. Semi-structured interview guides that explored baseline knowledge of cervical cancer, perceptions, and motivation for screening were used for in-depth interviews (IDIs). IDIs were conducted in the local language, Chichewa, translated and transcribed to English. Data was analyzed using NVivo® V12.0. Findings included fatalistic views on cancer, but limited knowledge specific to cervical cancer. Misconceptions of cervical cancer screening were common; however, there was a unique understanding of screening as prevention (i.e., finding and treating early disease to prevent progression to worsening disease). This understanding appeared to stem from HIV prevention concepts known to the community. Motivations for screening included desire to know one's health status, convenience of community-based screening, and peer encouragement. Despite limited knowledge of cervical cancer and misconceptions of screening, the concept of screening for prevention, desire to know one's health status, convenient access, and peers' influence were motivators for participation in screening. Cervical cancer screen-and-treat programs in high HIV prevalence areas should consider utilizing language that parallels HIV prevention language to communicate the need for cervical cancer screening and treatment and utilize prevention concepts that may already be familiar to women living there.